Desarrollo local y patrimonio cultural. El parque cultural de Albarracín - Rubio Terrado, Pascual (Geographicalia, 2015)
The cultural patrimony derives from the collective behavoir of a people in a place and a time and forms a part consubstantially of the territorial dimension. It constitutes an example of endogenous resource to which an high potential place of development is awarded in the local scale, in a double dimension, economic, as agent and mercantile by means of its tourist utilization, and social, aselement of identity. In Aragon, the Law 12/1997 of Cultural Parks contributes a own normative frame for the management-protection of the cultural patrimony from the generic purpose of the global sustainable arrangement of rural areas with patrimonial and landscape-environmental values which singularity constitutes an estructurante element of the territory. There proposes a model of economic and social alternative development productivist and related to the emergency of a postmodern approach of flexible multifunctionality. The development of the law has given place to the delimiting of five parks, among them that of Albarracín.
Keywords: Territorial resources; local sustainable development; cultural patrimony; cultural park; cultural tourism.